The role of Maqashid-Syariah in enhancing business sustainability through green dynamic capability and marketing strategies - Nurcahyo, Satria Avianda; Arismaya, Anisa Dewi; Anis, Muhammad (Indonesian Journal of Islamic Economics Research, 2024)
Abstract This study aims to explore the role of Maqashid Syariah in enhancing business sustainability through the integration of Green Dynamic Capability and marketing strategies, focusing on PT Bank Muamalat in the Central Java province. A quantitative research approach was employed, using the Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to analyze the relationships between variables. SEM PLS was chosen for its ability to evaluate complex models and measure latent variables that cannot be directly observed. Data were collected through a survey targeting 280 permanent employees of Bank Muamalat, using a saturated sampling technique to ensure comprehensive representativeness. The results of the study supported several hypotheses, showing that Maqashid Syariah positively influences marketing strategies and business sustainability. However, the impact of Green Dynamic Capability on innovation and business sustainability was not fully significant, indicating the need for further optimization in the implementation of green strategies. These findings suggest that Bank Muamalat can enhance its competitiveness by strengthening the application of Maqashid Syariah principles, particularly in marketing strategies, while simultaneously improving the integration of environmental sustainability initiatives. The study provides critical managerial implications, highlighting the importance of continuous monitoring and evaluation to ensure the effectiveness of these strategies in achieving long-term sustainability.